2014
DOI: 10.1186/1472-6955-13-26
|View full text |Cite
|
Sign up to set email alerts
|

Linking patient satisfaction with nursing care: the case of care rationing - a correlational study

Abstract: BackgroundImplicit rationing of nursing care is the withholding of or failure to carry out all necessary nursing measures due to lack of resources. There is evidence supporting a link between rationing of nursing care, nurses’ perceptions of their professional environment, negative patient outcomes, and placing patient safety at risk. The aims of the study were:a) To explore whether patient satisfaction is linked to nurse-reported rationing of nursing care and to nurses’ perceptions of their practice environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(94 citation statements)
references
References 49 publications
(76 reference statements)
3
86
0
5
Order By: Relevance
“…Likewise, the inverse significant association (p<0.01) found between the workload and the level of satisfaction of the patients with the care received by the nursing team is consistent with the results of other studies, which indicated that higher numbers of patients assigned to the nursing team decrease patient satisfaction and that the restriction or reduction of nursing staff has a negative repercussion on patients' and professionals' perception of safety in care environments (4)(5)(23)(24) . Despite the differences in context, working hours, professional training and others, studies in different countries indicated that the increase in the number of nurses and nursing hours in patient care, as well as a higher proportion of nurses in teams composed also by professionals with a vocational education can improve quality and safety outcomes for patients in hospitals.…”
Section: Discussionsupporting
confidence: 89%
“…Likewise, the inverse significant association (p<0.01) found between the workload and the level of satisfaction of the patients with the care received by the nursing team is consistent with the results of other studies, which indicated that higher numbers of patients assigned to the nursing team decrease patient satisfaction and that the restriction or reduction of nursing staff has a negative repercussion on patients' and professionals' perception of safety in care environments (4)(5)(23)(24) . Despite the differences in context, working hours, professional training and others, studies in different countries indicated that the increase in the number of nurses and nursing hours in patient care, as well as a higher proportion of nurses in teams composed also by professionals with a vocational education can improve quality and safety outcomes for patients in hospitals.…”
Section: Discussionsupporting
confidence: 89%
“…Responses were collected on a four‐point Likert‐type scale, and a “rationing score” was derived from the average sum of all items. A high degree of rationing was negatively associated with all five dimensions of patient satisfaction (Papastavrou, Andreou, Tsangari, et al., 2014). Schubert et al.…”
Section: Resultsmentioning
confidence: 99%
“…UFH invests in nurse training on the principle that quality nursing care has been shown to correlate positively with clinical outcomes and patient satisfaction. 12 Competitors have also realized the effectiveness of UFH's training programs and made the retention of junior nurses challenging for the company, particularly in Beijing, where nurses have received offers of up to double their UFH salaries.…”
Section: Clinical Personnelmentioning
confidence: 98%